El bienestar animal en las legislaciones de América Latina - León Guzmán, Marlen (2006)
Animal welfare has become a very important topic in international trade. This results from the debate about its legitimacy within the framework of the World Trade Organisation (WTO) regimen and within commercial practice. In Latin America, animal welfare is important in respect of trade, but also in the light of domestic requirements. The methodology of this composed by three phases: 1) the research and analyses of official norms concerning animal welfare; 2) the checked of the information by national authorities; 3) the discussion and comparison (of) them with the OIE’s Guidelines and other standards. This study was realized at 30th August 2005 in OIE General Headquarters, Paris. In general, Latin American regulation concerning animal welfare results from different causes and has different objectives. The causes leading to the development of animal welfare regulation are related to private commercial practice and the requirement of trade partners. Two types of current objectives were found: on the one hand domestic, and the other hand; international objectives. The principal differences between public regulation (national or international) are: 1) the methods of controlling animal welfare and 2) the use of certification as a means of confirming animal welfare measures.